Analysis Of The Effect Of Income Level And Work Motivation On The Work Productivity Of Truck Driver Employees At PT. Cahaya Sinar Gemilang - Perdana, Akbar; Samrin, Samrin (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
This study aims to analyze the effect of income level and work motivation on the work productivity of truck driver employees at PT Chahaya Sinar Gemilang. The research employs a quantitative approach using a survey method. The population as well as the sample consists of all truck driver employees totaling 45 respondents, selected using a saturated sampling technique. Data were collected through questionnaires using a Likert scale and analyzed with SPSS version 26. The data analysis techniques included validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, t-test, F-test, and coefficient of determination (R²). The results show that income level has a positive and significant effect on work productivity, as indicated by a t-value of 1.985 with a significance level of 0.045. Work motivation also has a positive and significant effect on work productivity, with a t-value of 5.221 and a significance level of 0.000. Simultaneously, income level and work motivation have a positive and significant effect on work productivity, proven by an F-value of 179.267 which is greater than the F-table value of 2.366, with a significance level of 0.000. The coefficient of determination (R²) of 0.895 indicates that 89.5% of the variation in work productivity is explained by income level and work motivation, while the remaining 10.5% is influenced by other factors outside the research model. This study provides practical contributions for company management in designing income policies and motivation strategies to improve employee productivity, as well as theoretical contributions to the development of human resource management studies in the transportation and logistics sector.